2009
DOI: 10.1128/aac.01031-09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antifungal Prophylaxis on Colonization and Azole Susceptibility of Candida Species

Abstract: Two large studies compared posaconazole and fluconazole or itraconazole for prophylaxis in subjects undergoing allogeneic hematopoietic stem cell transplantation or subjects with acute myelogenous leukemia. To assess the impact of prophylaxis on colonization and the development of resistance in Saccharomyces yeasts, identification and susceptibility testing were performed with yeasts cultured at regular intervals from mouth, throat, and stool samples. Prior to therapy, 34 to 50% of the subjects were colonized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 20 publications
3
55
0
3
Order By: Relevance
“…These differences in species distribution may be due to dissimilar antifungal use and prophylaxis practices, with a higher proportion of HSCT patients than of SOT patients in our study receiving antifungal prophylaxis (63% versus 15%). Multiple studies have suggested that the use of azoles can drive the species distribution within a population toward species with intrinsic resistance (1,8,10,16,26,33,34). Still, other factors may be contributing to this change in species distribution (27,32), and a few studies have shown no increase in the incidence of azole-resistant Candida species following azole prophylaxis (14,29).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in species distribution may be due to dissimilar antifungal use and prophylaxis practices, with a higher proportion of HSCT patients than of SOT patients in our study receiving antifungal prophylaxis (63% versus 15%). Multiple studies have suggested that the use of azoles can drive the species distribution within a population toward species with intrinsic resistance (1,8,10,16,26,33,34). Still, other factors may be contributing to this change in species distribution (27,32), and a few studies have shown no increase in the incidence of azole-resistant Candida species following azole prophylaxis (14,29).…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans is the main species associated with candidiasis, while Candida glabrata is one of the most predominant non- albicans species that has been linked to the development of oral infections [16]. It is an opportunistic pathogen in immunocompromised individuals [7,8], and it has an innate resistance to azoles [9,10]. C. glabrata differs from other pathogenic yeasts because of its phylogenetic position and haploid state with unconfirmed sexual cycle and diploid phase, contrary to C. albicans [11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of itraconazole and fluconazole prophylaxis in patients with AL have both been assessed in a number of placebo-controlled studies, the results of which have been mixed [2,3,7]. While prophylactic itraconazole and fluconazole may decrease Candida colonization overall, their prophylactic use has been associated with reports of resistant Candida colonization and breakthrough infections as well as significant drug interactions and toxicities [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%